Perancangan Sarana Media Informasi Berbasis Web Desa Klambir Lima Menggunakan Metode Waterfall - Hermansyah Hermansyah; Sri Wahyuni; Ahmad Akbar (STMIK Budi Darma, 2022)
The development of the current village government, especially the villages that are discussed in this study, namely Klambir Lima Kebun village, Hamparan Perak District, Deli Serdang Regency, is good with the village fund budget from the central government which aims to advance the village, the development of Klambir Lima Kebun village is currently inseparable from the support of information technology, almost every village needs information technology to improve services to the community. One example is the existence of an internet program in the village, the internet is currently not only enjoyed by urban people but has reached the village community. The difficulty of access to existing information makes researchers interested in developing a website-based Klambir Lima Kebun village information system with the aim of improving services to the people of Klambir Lima Kebun village, access to information can be obtained easily, village potential, population, area and so on. In making a web-based exam information system using the waterfall method consisting of analysis, design, coding and testing as well as entity relationship diagrams in designing databases. With this website-based information system, it can improve the services of Klambir Lima Kebun village to the community so that information to the community can be accessed easily and accurately. The information system is equipped with a web-based display so that users can adjust the contents in the system such as a web-based information system as a means of information in achieving development in Klambir Lima Kebun Village